Hospital utilization and telemedicine preferences in patients with late-stage Parkinson’s disease and caregivers - Seo Hyun Hong; Seoyeon Kim; Seungmin Lee; Bora Jin; Jung Hwan Shin; Kyung Ah Woo; Han-Joon Kim (Clinical Parkinsonism & Related Disorders)
Background: There remains a significant gap in systematic research on healthcare utilization behaviors and the influencing factors for patients with Parkinson’s disease (PD), particularly those in late stages. Methods: PD patients in late stage (Hoehn and Yahr (HY) stages 4 and 5) and their caregivers from Seoul National University Hospital Movement Disorders Clinic participated. A total of 103 respondents completed a questionnaire covering medical utilization behaviors, perceptions of face-to-face and telemedicine consultations, and additional medical service needs. Descriptive analysis was conducted based on HY stage, age, and travel time to the hospital. Results: 82.1% of patients in HY4 make more than 50% of in-person visits by themselves or with caregivers, compared with only 38.9% of patients in HY5. Despite proxy visits by caregivers were common, audiovisual or written materials about the patient’s condition were underused (63% answered ‘never’). Over three-quarters of patients did not receive rehabilitation therapy, mainly due to mobility issues and the lack of nearby facilities. One third of respondents were open to telemedicine, with differing preferences between age groups. 22% of HY5 patients or their caregivers were willing to pay more for telemedicine than in-person visit. Conclusion: This study seeks to understand hospital use patterns and needs in late-stage PD patients and their caregivers. Current treatment framework for PD has areas that, if improved, could significantly enhance the quality of care. Telemedicine offers an opportunity to enhance PD education and assessment, introducing new methods for remotely measuring symptoms.